Rest Tremor in Parkinson’s Disease is Associated with Increased Ipsilateral Striatal Dopamine Transporter Binding - Sunikka, Juha (My University, 2023)
The three cardinal motor symptoms of Parkinson’s disease include rigidity, bradykinesia, and rest tremor. Rigidity and bradykinesia are known to correlate with contralateral nigrostriatal degeneration and striatal dopamine deficit, but association between dopamine function and rest tremor has remained unclear. Here, the possible link between dopamine function and rest tremor was investigated using Parkinson’s Progression Markers Initiative (PPMI) dataset, the largest prospective neuroimaging cohort of patients with Parkinson’s disease. The processed data included clinical evaluations, [123I]-FP-CIT SPECT, and MRI images of 354 early PD patients and 166 healthy controls at baseline. A novel approach was employed allowing nonlinear registration of individual scans accurately to a standard space and voxelwise analyses. Association between the cardinal motor symptoms and tracer binding were investigated using voxelwise regression models. As expected, severity of both rigidity and bradykinesia were negatively correlated with contralateral striatal dopamine transporter (DAT) binding (PFWE<0.05). However, severity of rest tremor was associated with increased ipsilateral DAT binding (PFWE<0.05). The association between rest tremor and DAT binding remained the same when controlling for Hoehn & Yahr stage, MDS-UPDRS III score, bradykinesia-rigidity score, or motor phenotype. The association between rest tremor and DAT binding was independent from bradykinesia and rigidity, and was also replicated using 2-year follow-up data (PFWE<0.05). In agreement with the existing literature, a consistent association was not found between rest tremor and contralateral dopamine defect. These results demonstrate a link between rest tremor and increased ipsilateral DAT binding. These findings provide novel information about the dopaminergic correlates of parkinsonian tremor and may provide new insight into the neurobiological mechanisms of rest tremor.
Keywords: Parkinson’s disease, rest tremor, [123I]-FP-CIT SPECT, voxelwise analysis